Projected Economic Burden of Periprosthetic Joint Infection of the Hip and Knee in the United States - Premkumar, Ajay; Kolin, David A.; Farley, Kevin X.; Wilson, Jacob M.; McLawhorn, Alexander S.; Cross, Michael B.; Sculco, Peter K. (The Journal of arthroplasty, 2021)
In addition to the significant morbidity and mortality associated with periprosthetic joint infection (PJI), the cost of treating PJI is substantial. Prior high-quality national estimates of the economic burden of PJI utilize data up to 2009 to project PJI growth in the United States through 2020. Now in the year 2020, it is appropriate to evaluate these past projections and incorporate the latest available data to better understand the current scale and burden of PJI in the United States. The Nationwide Inpatient Sample (2002-2017) was used to identify rates and associated inpatient costs for primary total knee arthroplasty (TKA) and total hip arthroplasty (THA) and PJI-related revision TKA and THA. Poisson regression was utilized to model past growth and project future rates and cost of PJI of the hip and knee. Using the most recent data, the combined annual hospital costs related to PJI of the hip and knee were estimated to be $1.85 billion by 2030. This includes $753.4 million for THA PJI and $1.1 billion for TKA PJI, in that year. Increases in PJI costs are mainly attributable to increases in volume. Although the growth in incidence of primary THA and TKA has slowed in recent years, the incidence of PJI and the cost per case of PJI remained relatively constant from 2002 to 2017. Understanding the current and potential future financial burden of PJI for surgeons, patients, and healthcare systems is essential. There is an urgent need for efficacious preventive strategies in reducing rates of PJI after THA and TKA.